Ensinando professoras a analisar o comportamento do aluno: análise e interpretação de dados como parte de uma análise de contingências - Almeida, Carolina Porto de (2009)
Many studies about functional analysis (or contingency analysis) can be found in the literature and they are inserted in a diversity of research lines. The present study is part of a research line that employs the method proposed by Iwata, Dorsey, Slifer, Bauman e Richman (1982/1994) of systematic manipulation of environmental events for testing what happens to the frequency of the behavior of interest in a few sessions. The purpose of the current study was teaching school-teachers who had taken no prior courses and had no prior experience in behavior analysis to perform part of a contingency analysis: the analysis and the interpretation of data generated by the application of this method. Three preschool teachers participated in the study, all of which had students who presented behaviors considered inappropriate by the teachers. Data were collected in the school where the participants taught. Fourteen movies were used, with 9 minutes each one, that showed, in a simulated situation, one teacher implementing the method proposed by Iwata et al. (1982/1994) with one student who exhibited behaviors considered inappropriate. Seven movies showed the student s behavior maintained by a contingency of positive reinforcement (teacher s attention) and the other seven, by a contingency of negative reinforcement (escape from academic tasks). A training program was carried out in which the participants observed and recorded the occurrence or non occurrence of the student s target behavior (inappropriate behavior), the antecedent event and the consequence, on 30 second intervals. Then they answered five questions based on the records made, related to the data analysis and interpretation. The training included three phases: pre-test, training procedures and pos-test. The training procedure included the gradual removal of information, in which the register and the answers to all the questions were initially presented to the participants and, at each new step, one item of these models was removed. The pre-test results indicate that the participants made mistakes in the majority of the records about the three terms contingency at each 30 second interval. They also made the wrong interpretation about what was maintaining the behavior occurring in the movies exhibited. By comparing the results of the pre-test with those of the pos-test, in which they made correct records and correct interpretations in almost all the items, it is possible to say that the training procedure was effective to teach the participants to analyze and to interpret the recorded data. Based on the positive results about the performance of the participants, and considering that the maximum duration of the training was of 8 hours, it is possible to conclude that school-teachers can learn to perform part of a contingency analysis in a relatively short time when appropriately taught